Methods and Principles of Evaluation of Recreational Areas (Journal of Architectural Design, 2023)
In this article, the reconstruction of the first children's and youth recreation centre in the mountain landscape and recreational solution in the area of mountain ranges and their development based on the principles of architectural formation, mountain landscape and ecosystem, year-round work, work analysis, youth recreation centre and scientific- it was recommended to create the architecture of creative centres. Principles of placement of a children's and youth recreation centre in a recreational zone. Providing services to the population, providing employment and organizing national crafts and making souvenirs. Based on scientific research, an interesting and relevant conclusion is made in this field